Low plasma ghrelin levels in children with severe protein energy malnutrition - V., Harikrishnan; Kumar, Rakesh; Sachdeva, Naresh; Dayal, Devi (International Journal of Contemporary Pediatrics, 2018)
Background: Children with primary protein energy malnutrition (PEM) have significant loss of appetite which makes their nutritional rehabilitation difficult. Trials in patients with anorexia nervosa and cancer cachexia have shown short term efficacy of supplementing ghrelin to increase appetite. However, literature on ghrelin hormone status in children with PEM is scarce. We planned to study plasma ghrelin hormone levels in children with PEM and difference in plasma ghrelin levels among children having PEM of different grades. Methods: Cross-sectional observational study was conducted over one year period. All hospitalised children during the study period and fulfilling the inclusion criteria for primary PEM (WHO criteria for malnutrition) were enrolled as cases. The cases (59 children) were divided into 2 groups – (Group 1 -severe PEM, group 2 - mild to moderate PEM) and were compared with 19 healthy children as controls (Group 3). Plasma fasting ghrelin levels were measured using enzyme immunoassay. The results were analysed using Mann-Whitney U Test. Results: Median plasma ghrelin level among severe PEM group was 1.942ng/ml (interquartile range (IQR): 0.064, 9.506), mild to moderate PEM - 17.662 ng/ml (IQR: 1.658, 40.129) and controls - 17.525 ng/ml (IQR: 0.626, 27.361). Median ghrelin value was significantly lower in severe PEM group as compared to mild to moderate PEM (p value- 0.027). Conclusions: Plasma ghrelin levels are significantly reduced in children with severe PEM as compared with mild to moderate PEM and healthy controls.